E-Mail Sebagai Alat Komunikasi : Tahap Penggunaannya Di Kalangan Pegawai Dan Kakitangan Kementerian Pembangunan Usahawan - Mohamed Kamil, Mohamed (2002)

(untitled)
This study examines the level of e-mail usage among the officer and staff in Kementerian Pembangunan Usahawan Malaysia (KPUn). The objective of this study is to examine: i) The difference of the level of e-mail usage based on demographic factors. ii) The relationship between attitude factors with the level of e-mail usage. iii) The relationship between skill and knowledge factors with the level of email usage. iv) The relationship between attending course factors with the level of e-mail usage. v) The relationship between top management commitment factors with the level of e-mail usage. A set of questionnaire containing 40 items was used and data has been gathered from 50 officers and staffs in Kementerian Pembangunan Usahawan Malaysia (KPUn). The result of this study indicates that the level of e-mail usage is the middle and moving toward positive direction. There are no different level or significant between all factors except attitude factors show significant relationship with the level of e-mail usage.